Silencing of SNHG12 Enhanced the Effectiveness of MSCs in Alleviating Ischemia/Reperfusion Injuries via the PI3K/AKT/mTOR Signaling Pathway - Li, Yuanzhi; Guo, Shenquan; Liu, Wenchao; Jin, Tao; Li, Xifeng; He, Xuying; Zhang, Xin; Su, Hengxian; Zhang, Nan; Duan, Chuanzhi (Frontiers in Neuroscience, 2019)
Previous studies have reported that long non-coding RNA SNHG12 (lncRNA SNHG12) plays critical role in regulating biofunction of mesenchymal stem cells (MSCs), but the effect of lncRNA SNHG12 in MSCs in brain injury is still rarely reported. Hence, the protective effect and mechanism of a lncRNA SNHG12 modified mesenchymal stem cells (MSCs) was explored in treating brain injury under an ischemia/reperfusion (I/R) condition in this study. I/R rat brain microvascular endothelial cells (BMECs) were cocultured with MSCs or I/R pretreated MSCs. Then, proliferation of BMECs was detected using CCK-8 and EdU assays and apoptosis of cells was determined using flow cytometry and Hoechst. Autophagy of BMECs was determined using immunofluorescence and associated pathway was measured using western blotting. Moreover, proliferation, apoptosis, and autophagy of BMECs was also determined after co-culturing with shSNHG12-MSCs. In addition, a middle cerebral artery occlusion (MCAO) model rat model treated with MSCs injection was also used to confirm the findings in cells. I/R treatment significantly decreased the proliferation, but increase SNHG12 expression as well as the apoptosis and autophagy of BMECs. However, co-culturing with MSCs markedly alleviated the reduction of proliferation and increase of apoptosis and autophagy, as well as the phosphorylation of PI3K, AKT, and mTOR, in BMECs induced by I/R and shSNHG12 remarkably enhanced the effect of MSCs. In addition, MSCs injection also alleviated the infarct area and apoptosis of MACO rats, as well as the phosphorylation of PI3K, AKT, and mTOR. Moreover, shSNHG12 enhanced the ameliorative effect of MSCs in treating brain injury in MACO model.In conclusions, silencing SNHG12 enhanced the effect of MSCs in ameliorating apoptosis and autophagy of BMECs induced by PI3K/AKT/mTOR signaling pathway.